Eficiência Simbiótica de Rizóbios Isolados de Solos Amazônicos em Amendoim Forrageiro - Silva, Daniella de Vasconcelos da (Instituto Nacional de Pesquisas da Amazônia - INPA, 2021)
Arachis pintoi is a small legume, widely used in consortium with pasture, in the recovery of degraded areas, known for its good symbiotic association with nitrogen-fixing bacteria. Despite the potential use of this species, information on the selection of forage peanut strains adapted to the edaphoclimatic conditions of the Amazon region is still scarce. Thus, we sought to evaluate the symbiotic efficiency of rhizobia obtained from different soils in the Amazon region for Arachis pintoi cv. Amarillo in a greenhouse after 45 days, considering the control strains SEMIA 6439 and SEMIA 6440 recommended by the Ministry of Agriculture, Livestock and Supply under conditions of Brazilian Cerrado. For this purpose, this work was elucidated in the article entitled Symbiotic efficiency of rhizobia isolated from Amazonian soils in Peanut Forrageiro, presents results of the morphological characterization, biochemical tests, as well as the production of indolacetic acid and the symbiotic efficiency of the tested isolates. It was found that the majority of the isolates have morphological characteristics identical to the control strains, which showed red color in relation to the Gram stain test, with variation in the presence and absence of the oxidase and catalase enzymes. All strains produce indolacetic acid in varying amounts, twelve strains from different soils proved to be efficient in biological nitrogen fixation with a result superior to the recommended strains and the nitrogen control.
Keywords: Rizóbios